Relationship of socioeconomic differences between parents and IPS learning achievements - Yuni Indarwatiningsih; Sutarum (PPPM STKIP PGRI Lamongan, 2021)
The greater the family income the greater the chance of the family providing educational facilities for their children. If the level of income of parents is relatively good then all children's needs for school facilities and infrastructure will be met, so it is expected that the learning atmosphere of students is quite accommodated which in turn will be able to improve their learning achievement in school. The population in this study is the parents of students. sampling techniques using random sampling cluster techniques.Based on the results of the study, from the list of r-table values product moment in the observation case as much as 42 (N = 42) and with a degree of significance 5% known r-table value of 0.304. If this is compared to the R-count gain in this study of 0.857, then it is clearly known that the coefficient of r-count correlation is much greater than the r-table value at the level of 5% significance. further means that the nil hypothesis (H0) in this study should be rejected and vice versa the alternative hypothesis (Ha) whose proposition reads: It is suspected that there is a positive relationship between